Indo-Pacific: Bangladesh's Strategic Move to Geopolitics and Climate Security Concerns - Rakib, MD (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Bangladesh's foreign policy in the Indo-Pacific region is shaped by a delicate balancing act between global powers, notably the United States and China, while simultaneously addressing climate change and its security implications. This article explores the evolving nature of Bangladesh’s foreign policy, focusing on its engagement in the Indo-Pacific, its climate diplomacy, and its leadership role in multilateral forums like the Climate Vulnerable Forum (CVF). Drawing from Realist and Constructivist theoretical frameworks, the analysis underscores Bangladesh’s emphasis on securing national interests while promoting climate justice and regional stability. The article further examines the challenges Bangladesh faces due to climate-induced migration, security issues in the Bay of Bengal, and the emerging opportunities through blue economy initiatives. Future recommendations focus on strengthening multilateral engagement, expanding climate adaptation policies, and leveraging technology to enhance climate resilience. Bangladesh's strategic adaptability and leadership in both geopolitical and environmental arenas are crucial for its future security and prosperity.